Pengembangan Aplikasi Berbasis Mobile Android guna Menentukan Pola Makan bagi Pasien Penderita Penyakit Degeneratif - Stefano Zaghallo Sandah; Addin Aditya (Ikatan Ahli Informatika Indonesia, 2021)
Degenerative disease is a condition in which the function or structure of the affected tissue or organ has decreased over time. Degenerative diseases can be prevented by minimizing risk factors in individuals and one of them is by arranging a balanced and good diet in terms of nutrition or nutrition. This study aims to create a smartphone-based application that aims to determine the diet of people with degenerative diseases. Early detection of degenerative diseases is carried out using the forward chaining method, which is a rule-based system where the system will provide questions that represent a symptom in a particular disease. From the questions given, users get answers that will lead to other questions by forward chaining according to the symptoms (knowledge base) as facts of certain degenerative diseases. The final result of the forward chaining is the result of early detection or diagnosis by the system. The results of the initial detection or diagnosis are then used as food taboos. The diet is carried out independently by the user, where the food contained in the system is adjusted to meal times, food content, and degenerative diseases. From the results of the analysis, it can be concluded that the application can perform early detection of degenerative diseases and can display the diet according to the results of the forward chaining method.